PEMBERIAN PUPUK HAYATI DAN FOSFOR PADA PADI GOGO TERHADAP SERANGAN KEPIK HIJAU - Alfian Rusdy (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2010)
ABSTRACT The purposes of this study were to determine the resistance levels of non-irrigated rice to green bug (Nezara viridula L.) after providing bio-fertilizers and dosages of phosphorus. This research was carried out in the Experimental Farm of Research Center for Agricultural Technology (BPTP) NAD, Banda Aceh. The research applied a completely randomized factorial design with 2 treatments, i.e., 4 dosage levels of bio-fertilizers and 4 dosage levels of phosphorus. The results showed that the percentage of damaged plants, percentage of eating inhibition, and the percentage of infected spikelet showed a significant difference between treatments. The higher the dosages of bio-fertilizers and phosphorus were given, the lesser damage and the greater the eating inhibitions were recorded, and the smaller the grains were broken.